Health Funding Models for Maternal Health in European Countries: Challenges and Best Practices for Kenya (African Multidisciplinary Journal of Research, 2025)
Maternal health is a cornerstone of public health, reflecting how effectively a country’s health system serves its people. Yet across Europe, outcomes remain uneven despite substantial health spending, exposing persistent gaps in how funding models translate resources into equitable and quality maternal care. This study examines how five European countries, Germany, Sweden, France, Romania, and Italy, fund maternal healthcare, using the Control Knob Framework to assess which financing approaches perform best and where weaknesses persist. The research relied on a qualitative comparative case study design, 120 secondary sources that published from 2021-2023 were thematically analyzed. Sources included policy papers, government reports, datasets from the WHO and OECD, and peer-reviewed studies. The data were thematically analyzed through three lenses identified as financing architecture, governance and accountability and service delivery to identify key challenges, enablers and transferable lessons for Kenya. The results indicate that Sweden, Germany, and France have better maternal health outcomes due to an adequate and sustainable level of public investment, effective regulation, and a more equitable distribution of resources. They are able to achieve this by ensuring universal coverage of services through clear public accountability, community-based programs, and a manageable public-private financing structure. Conversely, Romania and some regions of Italy continue to function on fragmented and inadequate maternal financing, weak governance, and inequitable access to care, particularly with vulnerable populations. Overall, the way funds are organized and how they are managed significantly influences maternal health outcomes, more than the level of total spending. Systems that pool public and private financing under a clear accountability system achieve better coverage and quality services, while fragmented systems create inefficiency and inequities. In the case of Kenya, the findings point toward the potential benefit of a blended funding model, with strong regulatory oversight, clear allocation processes, and targeted investments in local regions to sustain maternal health financing, improve access, and diminish inequities.